Halal food supply chain issues in Malaysia halal food and beverages industry / Musdiana Mohamad Salleh and Etty Harniza Harun - Mohamad Salleh, Musdiana; Harun, Etty Harniza (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The word halal can be defined as anything which is permissible in Islam and good for human beings (Rahman, 2007). The rule is based on Islamic law, which enables Muslims to determine if products or services are halal. Halal (permitted) and the prevention of haram (forbidden) is one of the practices of Islam. Halal also provides guidelines on how to specifically consume goods for Muslims based on Islamic values. Muslims may only eat halal, though haram is forbidden, and doubtful items must be avoided (Haleem, Khan, Khan, & Jami, 2020; Rahman, 2007; Yusuf Al- Qaradawi, 1999) Halal supply chain is the management of halal network with the objective to extend the halal integrity from source to the point of consumer purchase (Standards Malaysia, 2019). According to Tieman (2011) maintaining a robust halal supply chain is a major challenge for all halal food producers, since the halal concept encompasses not only the sources of food ingredients, but also food processing and handling, packaging, storing, and delivering (Shah Alam & Mohamed Sayuti, 2011). Without a proper supply chain, there is no guarantee that halal products are truly halal at the point of consumption. Issues relating to halal, particularly on food consumption, have long been a source of contention. This paper attempts to address various issues in relation to halal food supply chain as well as indicate a gap in the literature and current practices.